Deletion of CRH From GABAergic Forebrain Neurons Promotes Stress Resilience and Dampens Stress-Induced Changes in Neuronal Activity - Dedic, Nina; Kühne, Claudia; Gomes, Karina S.; Hartmann, Jakob; Ressler, Kerry J.; Schmidt, Mathias V.; Deussing, Jan M. (Frontiers in Neuroscience, 2019)
Dysregulation of the corticotropin-releasing hormone (CRH) system has been implicated in stress-related psychopathologies such as depression and anxiety. Although most studies have linked CRH/CRH receptor 1 signaling to aversive, stress-like behavior, recent work has revealed a crucial role for distinct CRH circuits in maintaining positive emotional valence and appetitive responses under baseline conditions. Here we addressed whether deletion of CRH, specifically from GABAergic forebrain neurons (CrhCKO-GABA mice) differentially affects general behavior under baseline and chronic stress conditions. Expression mapping in CrhCKO-GABA mice revealed absence of Crh in GABAergic neurons of the cortex and limbic regions including the hippocampus, central nucleus of the amygdala and the bed nucleus of the stria terminals, but not in the PVN. Consequently, conditional CRH knockout animals exhibited no alterations in circadian and stress-induced corticosterone release compared to controls. Under baseline conditions, absence of Crh from forebrain GABAergic neurons resulted in social interaction deficits but had no effect on other behavioral measures including locomotion, anxiety, immobility in the forced swim test, acoustic startle response and fear conditioning. Interestingly, following exposure to chronic social defeat stress, CrhCKO-GABA mice displayed a resilient phenotype, which was accompanied by a dampened, stress-induced expression of immediate early genes c-fos and zif268 in several brain regions. Collectively our data reveals the requirement of GABAergic CRH circuits in maintaining appropriate social behavior in naïve animals and further supports the ability of CRH to promote divergent behavioral states under baseline and severe stress conditions.